Brief Report: Self-Reported Knowledge of HIV Status Among Cisgender Male Sex Partners of Transgender Women in Lima, Peru. (1st May 2022) - Long, Jessica E.; Sanchez, Hugo; Dasgupta, Sayan; Huerta, Leyla; Garcia, Dania Calderón; Lama, Javier R.; Duerr, Ann
Abstract : Background: Knowledge of HIV status is a critical first step in the HIV care cascade. Cisgender male sex partners of transgender women (MSTW) are at a disproportionately high risk of HIV, but little is known about their access to HIV testing or knowledge of HIV status. Methods: We used cross-sectional data from a respondent-driven sampling study to analyze self-reported HIV status and predictors of knowledge of HIV status among MSTW in Lima, Peru. Mixed-effects models were used to generate crude and adjusted prevalence ratios (aPRs) and 95% confidence intervals (CIs) for the association between knowledge of HIV status and predictors of interest, including sociodemographics and recent sexual behavior. Results: From February to July 2018, 196 eligible MSTW enrolled, of which 90 (46%) reported not knowing their HIV status. Recent casual or 1-time partners were reported by 84% of MSTW and 54% reported purchasing sex. In adjusted analyses, MSTW participants were less likely to know their HIV status if they reported buying sex (aPR 0.43, 95% CI: 0.32 to 0.59) or reported ≥16 recent sex partners compared with ≤5 partners [aPR 0.32, (0.20 to 0.50)]. Those who reported male sex partners were 80% more likely to know their status [aPR 1.80, (1.33 to 2.44)]. Conclusions: Reported knowledge of HIV status was low among MSTW in Lima, and unknown HIV status was associated with behaviors linked to HIV acquisition. MSTW who reported male partners were more likely to know their status, potentially indicating that HIV testing is more accessible to men who have sex with men.